2013
DOI: 10.1098/rspb.2013.1065
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection accelerates signal evolution during speciation in birds

Abstract: Sexual selection is proposed to be an important driver of diversification in animal systems, yet previous tests of this hypothesis have produced mixed results and the mechanisms involved remain unclear. Here, we use a novel phylogenetic approach to assess the influence of sexual selection on patterns of evolutionary change during 84 recent speciation events across 23 passerine bird families. We show that elevated levels of sexual selection are associated with more rapid phenotypic divergence between related li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(236 citation statements)
references
References 57 publications
11
222
3
Order By: Relevance
“…Lack of robust phylogenies for Amazonian birds precluded us from incorporating tree topologies and branch lengths into our models. Thus, to control for phylogenetic nonindependence, we included taxonomy (genus nested within family) as a random effect, following numerous studies (57,58). In all cases, the mixed-effects model including taxonomy [family (genus)] had a significantly lower log-likelihood score than the model excluding taxonomy (Table S5).…”
Section: Methodsmentioning
confidence: 99%
“…Lack of robust phylogenies for Amazonian birds precluded us from incorporating tree topologies and branch lengths into our models. Thus, to control for phylogenetic nonindependence, we included taxonomy (genus nested within family) as a random effect, following numerous studies (57,58). In all cases, the mixed-effects model including taxonomy [family (genus)] had a significantly lower log-likelihood score than the model excluding taxonomy (Table S5).…”
Section: Methodsmentioning
confidence: 99%
“…The striking colours of birds, and especially the large differences in colour across males of sexually dimorphic species, are thought to be a result of sexual selection [1]. Theories about how sexual selection drives the evolution of colour fall into three general classes.…”
Section: Introductionmentioning
confidence: 99%
“…In fishes and butterflies, variation in visual pigments has been implicated in mate choice, thereby shaping the evolution of male colours [12,19,24]. Birds are a notably colourful group, and have been the subject of many classic studies of sexual selection [1,25], that have shown plumage colour is used as a mating signal. To date, associations between birds' visual system and the evolution of plumage colour have been rarely studied ( [26,27], reviewed in [2]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, dimorphisms in both song and plumage colors have been shown to be associated with an assortment of life history traits besides mating system, including breeding latitude, seasonal migration, nesting behavior, and territoriality (Martin and Badyaev, 1996;Friedman et al, 2009;Price, 2009;Soler and Moreno, 2012;Johnson et al, 2013;Odom et al, 2015). Nevertheless, the perception that levels of sexual dimorphism reflect levels of sexual selection remains pervasive, even among some researchers (e.g., Seddon et al, 2013;Bloch, 2015).…”
Section: Sexual Dimorphism Is Not Due To Sexual Selection Alonementioning
confidence: 99%